Fractionation of Pinus radiata wood by combination of steam explosion and organosolv delignification - Camila María Imlauer-Vedoya (Maderas. Ciencia y Tecnología, 2019)
This work proposes a sequential combination of steam explosion and organosolv delignification for Pinus radiata fractionation. An efficient pretreatment to fully optimize the use of lignocellulosic materials is the key to make a biorefinery profitable, especially for softwoods, known to be more recalcitrant than other lignocellulosic raw materials. Steam explosion has a dual effect on biomass as morphological and chemical changes are introduced. A delignifying stage has been stated to be necessary in order to ease hydrolytic enzymes accessibility to cellulose while avoiding non-productive bonds with the lignin present. Three steam explosion conditions were tested (170°C, 5 min; 180°C, 10 min; 170°C, 5+5 min) followed by an organosolv delignification stage, carried out at two different conditions (170°C, 60 min; 170°C, 90 min). All treatment yields, delignification extent, and hydrolysis yields were determined to evaluate each stage. The steam explosion treatment did not produce high delignification extent. Maximum global delignification (50,4%) was achieved when combining the two-cycle steam explosion with the most severe post-treatment condition tested. Enzymatic hydrolysis of the cellulosic residue improved after organosolv delignification; however, hydrolysis yields did not exceed 35%. The chemical changes undergone by softwood lignins are presumably responsible for the low digestibility.